Studies in the Trial by River Ordeal in the Ancient Near Kast During the Second Millennium B.C.B. - Lieberman, Alvin I.
Dissertation; Microfilm $3; Xerox $9.70. Cf. Dissertation Abstracts 30 (1969-70) 2449-A.